Improving early detection of gastric cancer: a novel systematic alphanumeric-coded endoscopic approach - Emura, Fabian; Gralnek, Ian; Baron, Todd H (Revista de gastroenterología del Perú, 2013)
Despite extensive worldwide use of standard esophagogastroduodenoscopy (EGD) examinations, gastric cancer (GC) is one of the most common forms of cancer and ranks as the most common malignant tumor in East Asia, Eastern Europe and parts of Latin America. Current limitations of using non systematic examination during standard EGD could be at least partially responsible for the low incidence of early GC diagnosis in countries with a high prevalence of the disease. Originally proposed by Emura et al., systematic alphanumeric-coded endoscopy (SACE) is a novel method that facilitates complete examination of the upper GI tract based on sequential systematic overlapping photo-documentation using an endoluminal alphanumeric-coded nomenclature comprised of eight regions and 28 areas covering the entire surface upper GI surface. For precise localization or normal or abnormal areas, SACE incorporates a simple coordinate system based on the identification of certain natural axes, walls, curvatures and anatomical endoluminal landmarks. Efectiveness of SACE was recently demonstrated in a screening study that diagnosed early GC at a frequency of 0.30% (2/650) in healthy, average-risk volunteer subjects. Such a novel approach, if uniformly implemented worldwide, could significantly change the way we practice upper endoscopy in our lifetimes.